2018
DOI: 10.1007/s12035-018-1391-3
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Serum Lipid Profiles to Outcome After Endovascular Thrombectomy for Anterior Circulation Ischemic Stroke

Abstract: The contribution of lipids, including low- and high-density lipoprotein cholesterol (LDL-C and HDL-C, respectively) and triglycerides (TG), to stroke outcomes is still debated. We sought to determine the impact of LDL-C concentrations on the outcome of patients with ischemic stroke in the anterior circulation who received treatment with endovascular thrombectomy (EVT). We performed a retrospective analysis of consecutive patients with acute ischemic stroke treated at a tertiary center between 2012 and 2016. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Biomarkers detected in the peripheral blood of patients could have better predictive values because they are often related to pathophysiological response to EVT recanalization. In this regard, matrix metalloprotease-9 [ 6 ] and low-density lipoprotein cholesterol [ 33 ] have been associated with clinical outcomes in EVT-treated AIS patients. Senchenkova et al [ 20 ] have shown that plasma levels of ANXA1 were lower in AIS patients than healthy controls, but the study did not link the finding to clinical outcomes of the AIS patients and those with EVT.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers detected in the peripheral blood of patients could have better predictive values because they are often related to pathophysiological response to EVT recanalization. In this regard, matrix metalloprotease-9 [ 6 ] and low-density lipoprotein cholesterol [ 33 ] have been associated with clinical outcomes in EVT-treated AIS patients. Senchenkova et al [ 20 ] have shown that plasma levels of ANXA1 were lower in AIS patients than healthy controls, but the study did not link the finding to clinical outcomes of the AIS patients and those with EVT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with higher cholesterol levels exhibit lower mortality after stroke [71]. High LDL-C levels early in the course of a stroke following large artery occlusion in the anterior circulation correlate with better clinical outcomes at 3 months [72]. The Basilar Artery International Cooperation Study (BASICS) found that hyperlipidemia corre- lates with better outcomes after BAO [73].…”
Section: Discussionmentioning
confidence: 99%
“…There was a discrepancy in the prognostic significance between LDL-C level and outcomes in AIS patients [ 1 – 11 ]. Some studies found that higher LDL-C level was associated with poor outcomes in AIS patients [ 1 – 3 ], while some studies found that lower LDL-C was associated with poor outcome in AIS patients [ 4 , 5 ], others failed to find a significant association between LDL-C and outcome [ 6 11 ]. The inconsistent results might be explained by differences in sample size, patient selection, potential confounder, outcome assessment, and different measurement times of LDL-C. Several studies suggested that LDL got oxidized into oxLDL under oxidative stress [ 19 ], and oxLDL may contribute to exacerbate free-radical damage in the acute phase of AIS [ 20 , 32 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since AIS patients may suffer from enhanced free-radical damage after reperfusion therapy [ 12 , 13 ], focusing on patients with reperfusion therapy might clarify the role of LDL-C. However, previous studies on the association between LDL-C level and outcomes in AIS patients with reperfusion therapy failed to reach a consensus [ 5 8 ]. The conflicting conclusions may be due to the single measurement of LDL-C.…”
Section: Introductionmentioning
confidence: 99%